2020
DOI: 10.1111/cdev.13348
|View full text |Cite
|
Sign up to set email alerts
|

Shared Book Reading in Preschool Supports Bilingual Children’s Second‐Language Learning: A Cluster‐Randomized Trial

Abstract: This cluster-randomized controlled study examined dual language learners (DLLs) in Norway who received a book-based language intervention program. About 464 DLLs aged 3-5 years in 123 early childhood classrooms participated in the study. The children were acquiring Norwegian as their second language in preschool and spoke a variety of first languages at home. They received a researcher-developed intervention that was organized around loosely scripted, content-rich shared reading in school and at home. Receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 54 publications
1
19
0
3
Order By: Relevance
“…These differences in proficiency can pose challenges to DLLs’ academic achievement in addition to socioeconomic risk factors or immigration experiences which disproportionally affect DLLs (Hoff, 2013; Mullis, Martin, Foy, & Hooper, 2017; NASEM, 2017; OECD, 2018). Against this backdrop, improving DLLs’ chances to gain stronger majority language skills before school entry has become a focus of early childhood education (ECE) programs (Buysse, Peisner‐Feinberg, Páez, Hammer, & Knowles, 2014; Grøver, Rydland, Gustafsson, & Snow, 2020; Larson et al., 2020; Walker et al., 2020; Yazejian, Bryant, Freel, Burchinal, & Educare Learning Network Investigative Team, 2015). Crucially, research has shown that ECE programs can succeed in promoting DLLs’ second language skills while offering opportunities for DLLs to maintain and strengthen verbal and literacy skills in their first language (Barnett, Yarosz, Thomas, Jung, & Blanco, 2007; Durán, Roseth, Hoffman, & Robertshaw, 2013; Slavin, Madden, Calderón, Chamberlain, & Hennessy, 2011) which substantially contribute to DLLs’ later academic achievement as well (Edele & Stanat, 2016).…”
Section: Effects Of Preschool Experiences On Dlls’ Language Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences in proficiency can pose challenges to DLLs’ academic achievement in addition to socioeconomic risk factors or immigration experiences which disproportionally affect DLLs (Hoff, 2013; Mullis, Martin, Foy, & Hooper, 2017; NASEM, 2017; OECD, 2018). Against this backdrop, improving DLLs’ chances to gain stronger majority language skills before school entry has become a focus of early childhood education (ECE) programs (Buysse, Peisner‐Feinberg, Páez, Hammer, & Knowles, 2014; Grøver, Rydland, Gustafsson, & Snow, 2020; Larson et al., 2020; Walker et al., 2020; Yazejian, Bryant, Freel, Burchinal, & Educare Learning Network Investigative Team, 2015). Crucially, research has shown that ECE programs can succeed in promoting DLLs’ second language skills while offering opportunities for DLLs to maintain and strengthen verbal and literacy skills in their first language (Barnett, Yarosz, Thomas, Jung, & Blanco, 2007; Durán, Roseth, Hoffman, & Robertshaw, 2013; Slavin, Madden, Calderón, Chamberlain, & Hennessy, 2011) which substantially contribute to DLLs’ later academic achievement as well (Edele & Stanat, 2016).…”
Section: Effects Of Preschool Experiences On Dlls’ Language Developmentmentioning
confidence: 99%
“…These differences in proficiency can pose challenges to DLLs' academic achievement in addition to socioeconomic risk factors or immigration experiences which disproportionally affect DLLs (Hoff, 2013;Mullis, Martin, Foy, & Hooper, 2017;NASEM, 2017;OECD, 2018). Against this backdrop, improving DLLs' chances to gain stronger majority language skills before school entry has become a focus of early childhood education (ECE) programs (Buysse, Peisner-Feinberg, Páez, Hammer, & Knowles, 2014;Grøver, Rydland, Gustafsson, & Snow, 2020;Larson et al, 2020;Walker et al, 2020;Yazejian, Bryant, Freel, Burchinal, & Educare Learning Network Investigative Team, 2015). Crucially, research has shown that ECE programs can succeed in promoting DLLs' second language skills while offering opportunities for growth trajectories (above and beyond differences related to socioeconomic status [SES]), (b) to what extent the effect of the home language status on majority language skills varies between preschool classrooms, and (c) whether the skill levels of classroom peers have differential effects on the development of majority language skills for DLLs and monolingual children (controlling for classroom quality).…”
mentioning
confidence: 99%
“…The target children were recruited through their preschools as part of a larger language-based intervention study (Grøver, Rydland, Gustafsson & Snow, 2020). In the present study, we use the pre-intervention data that were collected as part of the overall project.…”
Section: Samplementioning
confidence: 99%
“…Vocabulary is a fundamental component of learning to read (National Reading Panel, 2000). Some studies have shown the importance of shared reading in developing vocabulary (Sénéchal & LeFevre, 2014; Grøver, Rydland, Gustafsson, & Snow, 2020), whether productive vocabulary or receptive vocabulary (Mol, Bus, de Jong, & Smeets, 2008). The National Early Literacy Panel (2008) also showed that shared reading promotes the acquisition of several components of oral language, especially vocabulary.…”
Section: Vocabularymentioning
confidence: 99%